(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article describes the trends in the development of regional agriculture in the Andijan region in 2010-2019 based on economic and statistical analysis of the main indicators. On the basis of the identified trends of the changes of the territory, determined the directions of agricultural development of regional branch.